2012
DOI: 10.1080/1360080x.2012.716003
|View full text |Cite
|
Sign up to set email alerts
|

Student satisfaction and student perceptions of quality at international branch campuses in the United Arab Emirates

Abstract: The international branch campus has emerged as a popular form of transnational higher education but to date little research has been undertaken on student perceptions and experiences, other than the student feedback evaluations conducted by institutions. This research employed a survey questionnaire to investigate student perceptions of study at international branch campuses in the United Arab Emirates (UAE), the country which hosts the largest number of branch campuses globally. Across the seven dimensions ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 29 publications
1
55
0
5
Order By: Relevance
“…In the case of the United Arab Emirates, the location of the programme studied here, English is often not the first language of the lecturers, either (Wilkins, Stephens Balakrishnan, & Huisman, 2012). Furthermore, Robson (2011) argues that international staff will need to examine their 'habitual practices' of teaching and that a critical stance towards their pedagogy needs to be nurtured through self-reflection.…”
Section: Staff Development Programmesmentioning
confidence: 99%
“…In the case of the United Arab Emirates, the location of the programme studied here, English is often not the first language of the lecturers, either (Wilkins, Stephens Balakrishnan, & Huisman, 2012). Furthermore, Robson (2011) argues that international staff will need to examine their 'habitual practices' of teaching and that a critical stance towards their pedagogy needs to be nurtured through self-reflection.…”
Section: Staff Development Programmesmentioning
confidence: 99%
“…UAE hosts the largest number of branch campuses globally, with high rates of student satisfaction [21]. The Kingdom of Saudi Arabia has been working collaboratively with Canada on transnational education efforts since 2003, with King Fahd University in Dhahran building e-learning initiatives with the University of British Columbia [13].…”
Section: Transnational Initiativesmentioning
confidence: 99%
“…The current literature on the importance of student satisfaction abounds with a considerable number of examples. Prior studies (Kallio, 1995;Elliott & Healy, 2001;Wilkins et al, 2012) suggest that students' overall experience is strongly associated with campus climate, student-centeredness, campus social life and institutional effectiveness. Recent studies (Aldemir & Gülcan, 2004;Denson et al, 2010;Sojkin et al, 2012;de Jager and Gbadamosi, 2013;Sivis-Cetinkaya, 2013;Beck et al, 2014;Min & Koon, 2014;Zhang et al, 2014) found that female students tended to have more satisfaction than male counterparts, whereas a most recent work (Sarrico & Rosa, 2014) put forward that male students and freshmen were more satisfied groups.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…On the other hand, age was found (Aldemir & Gülcan, 2004;Sojkin et al, 2012;Min & Koon, 2014) as a crucial factor influencing students' satisfaction with higher education services. A number of studies (Kwan & Ng, 1999;Mai, 2005;Gamage et al, 2008;Wilkins et al, 2012;de Jager & Gbadamosi, 2013;Min & Koon, 20014) accomplished several comparisons of student satisfaction between selected countries in various quality aspects. Another study (Moro-Egido & Panades, 2010) found that students who hold a part-time job were more likely to have less satisfaction.…”
Section: Review Of Related Literaturementioning
confidence: 99%